A new combination in African Gymnanthes (Euphorbiaceae) - Esser, Hans-Joachim (Phytotaxa, 2018)
The genus Gymnanthes Swartz (1788: 6, 95), originally considered as Neotropical (Pax & Hoffmann 1912), has recently been expanded to include species from Africa and Asia (Esser 1999, 2001). Previously, the two African species had been included in the separate genus Duvigneaudia Léonard (1959: 15), and were as such revised by Kruijt & Roebers (1996). Léonard (1959) had described the genus because these species were clearly distinct from all other African genera, but he did not compare any Neotropical plants, much like Kruijt & Roebers (1996). Also the World Checklist of Euphorbiaceae (Govaerts et al. 2000) accepted the genus as distinct. However, the African species hardly differ from many species of Neotropical Gymnanthes by any significant characters of the leaves and flowers, and although they have somewhat larger fruits, this does not seem to be sufficient to uphold Duvigneaudia as a separate genus. Therefore both genera were united by Esser (1999, 2001). Within Neotropical Gymnanthes, Duvigneaudia is most similar to the former genus Sarothrostachys Klotzsch (1841) from Brazil.